2018
DOI: 10.1074/jbc.m117.811299
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-activated epidermal growth factor receptor (EGFR) signaling governs endocytic trafficking of unliganded receptor monomers by non-canonical phosphorylation

Abstract: Epidermal growth factor receptor (EGFR), one of the most characterized receptor tyrosine kinases (RTKs), regulates many cellular functions, including survival, proliferation, and differentiation. The aberrant activation of EGFR by overexpression or activating mutations is a major mechanism underlying the pathogenesis of human cancers, including colorectal and lung cancers, and participates in acquired resistance to anti-cancer agents (1-4).Ligand-bound EGFR proteins form an asymmetric homodimer on the plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 45 publications
7
68
0
Order By: Relevance
“…We recently demonstrated that TNF-α-induced endocytosis occurred on inactive monomeric EGFR in a TK-independent manner using a dimer-deficient EGFR mutant (dd-EGFR) lacking extra-and intracellular dimerization sequences (9,18,23,24). We detected the cisplatin-induced phosphorylation of dd-EGFR at Ser-1015 and Ser-1047 (Fig.…”
Section: Cisplatin-induced Egfr Endocytosis Via Ser-1015 Phosphor Ylamentioning
confidence: 99%
“…We recently demonstrated that TNF-α-induced endocytosis occurred on inactive monomeric EGFR in a TK-independent manner using a dimer-deficient EGFR mutant (dd-EGFR) lacking extra-and intracellular dimerization sequences (9,18,23,24). We detected the cisplatin-induced phosphorylation of dd-EGFR at Ser-1015 and Ser-1047 (Fig.…”
Section: Cisplatin-induced Egfr Endocytosis Via Ser-1015 Phosphor Ylamentioning
confidence: 99%
“…Evidence from our own and previous studies suggests that the ERK (partially JNK) pathway plays a pivotal role in scratch/EGFR-mediated CCL20 production. Although p38 MAPK is not directly involved in scratch-induced CCL20 production, a recent study suggests that p38 MAPK may regulate the recycling of EGFR by accelerating the latter's endocytosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, EGFR still has serine/threonine phosphorylation sites, which also play important roles in EGFR regulation, including EGFR endocytosis. 28,29 We found that DPBA had no effect on EGFR serine/ threonine phosphorylation level, indicating that Ser/Thr phosphorylation may not be involved in DPBA-induced EGFR endocytosis ( Supplementary Fig. 2c).…”
Section: Dpba Decreases Egfr Protein Levels By Lysosomal Degradationmentioning
confidence: 90%